Teacher training academic programs for gifted and talented students - Marsyl Bulkool Mettrau (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This article presents a discussion of important issues on high skills, talent, creativity, care programs/academic enrichment and production from the Postgraduate Specialization Course (Master and Doctorate), taught in the State University Rio de Janeiro/UERJ (Brazil) until 2004. It deals with conceptual aspects of high abilities, talent, creativity and enrichment programs that followed logico-creative methodologies (RATHS, 1977; DE BONO, 1982, 1985). Its objectives are to highlight two paths: a) to establish and manage groups to respond to students with high abilities/gifted students; b) to conduct research and write theses related to these issues and the relationship between attention and research.